Symptoms in the masticatory system and related quality of life in prospective orthognathic patients - Riikka Pietilä; Mimmi Tolvanen; Timo Peltomäki; Anna-Liisa Svedström-Oristo (Taylor and Francis Ltd, 2022)
Objective: The aim of this study was to investigate the relation between orthognathic patients’ self-reported symptoms in the head and neck region and their quality of life (QoL).
Material and methods: Participants included were consecutive patients (n = 50) referred to the assessment of orthognathic treatment need and voluntary first-year university students (n = 29). All participants filled in the Orthognathic Quality of Life Questionnaire (OQLQ) and a structured diary created by the authors. The median values of Orthognathic Quality of Life (OQOL) sum and subscores, satisfaction with oral function and number of awakenings were compared between patients and controls. Further, correlations between the OQOL sum and subscores, satisfaction with oral function and number of awakenings were analyzed.
Results: Patients reported significantly more symptoms (p = .013) and woke up significantly more often than the controls (p = .032). Their OQOL sum scores were significantly higher (indicating a lower OQOL) (p = .001), and they were significantly less satisfied with their oral function than the controls (p < .001). Among the awakened and not-rested patients, the most commonly reported symptoms were pain in the head and/or neck region and fatigue and/or stiffness in the jaws.
Conclusions: Experiences of pain and discomfort have a significant impact on patients’ OQOL and well-being.